Between tough voyages and empowering tourism: Can Muslim Bugis seafarers tackle the maritime-sector crises in Indonesia? - Abdur Rozaki (SIMULACRA: JURNAL SOSIOLOGI, 2022)
This paper explores the shift in commercial sailing by the Muslim coastal community of the ethnic Bugis—from their past focus on inter-island and international commerce to maritime tourism that is limited to the Eastern Indonesian region for domestic and foreign tourists. Using historical and phenomenological approaches, this paper explains a series of arduous crises to show the dignity and prosperity of the great maritime tradition among commercial seafarers, who, during the Islamic empire from the 15th to 17th century, experienced glory for being able to control and manage maritime commerce. Ever since the presence and success of the Europeans, especially the Dutch, in controlling Nusantara (the Indonesian archipelago), the glory of Muslim seafarers’ trade voyages has dwindled and narrowed, both in terms of the number of ships, types, and tonnage of cargo, as well as their cruising range. Although the Indonesian government has not systematically and comprehensively formulated policies to restore the glory in the maritime sector so far, tourism development policies have been welcomed by the Muslim Bugis seafarers as a new opportunity to empower the family economy.